The Hidden Benefits of Being an Involved Father - Kate Fogarty; Garret D. Evans (EDIS)
Revised! FCS2137, a 5-page fact sheet by Kate Fogarty and Garret D. Evans, describes the benefits for children, fathers, and families when the father is more involved with his children. Includes references. Published by the UF Department of Family Youth and Community Sciences, November 2009.